Reversal of tooth eruption sequence: beliefs and perceptions (2019)
Among some Nigerians, eruption of the maxillary primary incisors before their mandibular counterparts is considered a taboo. Data regarding the perceptions of residents of Igbo Ora to reversal of eruption sequence appear non-existent. The aim of this study is to assess the attitudes and beliefs of some adults of Igbo Ora to reversal of eruption sequence of primary incisors A cross-sectional study was conducted among community dwelling females aged 18 years and older in Igbo Ora, Southwestern Nigeria. A house to house survey was conducted among all willing adult females available at the time of the study. Data for the study was collected with an interviewer administered questionnaire in the Yoruba Language. Data collected were analyzed with SPSS version 21. Frequencies, means and proportions were generated and test of association between categorical variables was done using Chi Square statistics. There were 229 participants with a mean age of 34.6 (SD = 12.6) years and majority ( 34.1%) had secondary school education . Reversal of eruption sequence was attributed to child being evil (47.6%) and mother exposed to other evil children (4.8%). About 56.3% of respondents believe that reversed eruption sequence has a negative effect on the child, including the ability to place irrevocable curses on people. A perceived consequence of having a child with reversed tooth eruption sequence on the family was fear of the child by other family members (21.8%). Beliefs about reversed sequence of eruption of primary anterior teeth being a normal variation increased with educational qualification (p = 0.001). The study has revealed gross fallacies regarding reversal of eruption sequence in children in Igbo Ora. Health education intervention should be given to them particularly targeting mothers and the less educated